2017
DOI: 10.1038/nmicrobiol.2017.65
|View full text |Cite
|
Sign up to set email alerts
|

Zooming in on the phycosphere: the ecological interface for phytoplankton–bacteria relationships

Abstract: By controlling nutrient cycling and biomass production at the base of the food web, interactions between phytoplankton and bacteria represent a fundamental ecological relationship in aquatic environments. Although typically studied over large spatiotemporal scales, emerging evidence indicates that this relationship is often governed by microscale interactions played out within the region immediately surrounding individual phytoplankton cells. This microenvironment, known as the phycosphere, is the planktonic a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

16
852
2

Year Published

2018
2018
2024
2024

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 852 publications
(870 citation statements)
references
References 145 publications
16
852
2
Order By: Relevance
“…The potential capacity of bacteria to use chemotaxis to take advantage of this microenvironment is notable given that marine heterotrophic bacteria obtain a large fraction of their carbon demand directly from phytoplankton, consuming up to 50% of phytoplankton-fixed carbon 21 . Recent studies using microfluidic experiments 22 and direct microscopic observations of chemotactic bacteria aggregating around phytoplankton cells 16 support predictions that bacterial chemotaxis will enhance bacterial uptake of phytoplankton derived carbon, as well as potentially underpinning the establishment and maintenance of important phytoplankton-bacteria relationships in the ocean 20 .…”
mentioning
confidence: 83%
See 2 more Smart Citations
“…The potential capacity of bacteria to use chemotaxis to take advantage of this microenvironment is notable given that marine heterotrophic bacteria obtain a large fraction of their carbon demand directly from phytoplankton, consuming up to 50% of phytoplankton-fixed carbon 21 . Recent studies using microfluidic experiments 22 and direct microscopic observations of chemotactic bacteria aggregating around phytoplankton cells 16 support predictions that bacterial chemotaxis will enhance bacterial uptake of phytoplankton derived carbon, as well as potentially underpinning the establishment and maintenance of important phytoplankton-bacteria relationships in the ocean 20 .…”
mentioning
confidence: 83%
“…This behaviour is also involved in pathogenicity and disease outbreaks among a wide range of marine species 32,33 , both in natural habitats 27 and in aquaculture settings 34 , sometimes with dire ecological and economic consequences. In the pelagic environment, chemotaxis plays an often pivotal role in all major biogeochemical cycles, by affecting the rates and directions of key chemical transformations 1,9,20 . For example, chemotaxis-mediated particle colonisation influences controls the amount of carbon that either sinks to the deep sea or is respired in the upper ocean, ultimately influencing global carbon budgets …”
Section: Host Associationsmentioning
confidence: 99%
See 1 more Smart Citation
“…While numerous studies concentrate on the causes of HABs, few have considered that bacterial species coexisting with microalgae could contribute to their development. However since Bell and Mitchell reported that specific bacterial communities occur and microbial activity was altered in the so-called phycosphere (Bell and Mitchell, 1972;Bell and Lang, 1974), more and more studies suggest that such algalbacterial interactions are very specific and important (Azam and Malfatti, 2007;Amin et al, 2015;Bertrand et al, 2015;Ramanan et al, 2016;Seymour et al, 2017). A plausible hypothesis suggests that the mutualistic association of some phytoplankton and bacteria is based on nutrient exchange.…”
Section: Introductionmentioning
confidence: 99%
“…Recently, Behringer et al (2018) demonstrated that bacterial communities on diatom surfaces displayed strong conservation across diatom strains. Seymour et al (2017) elegantly summarized the main corresponding mechanisms and processes, which show an impressive array of diversity and complexity.…”
Section: Introductionmentioning
confidence: 99%